Towards a complete structural deciphering of Type VI secretion system. (April 2018) - Nguyen, Van Son; Douzi, Badreddine; Durand, Eric; Roussel, Alain; Cascales, Eric; Cambillau, Christian
Graphical abstract: Highlights: Type VI secretion system (T6SS) is a bacterial system that injects toxins in preys. The T6SS contractile tail is attached to the membrane complex via a baseplate. Structures of the membrane complex and tail have been determined. Cryo-EM tomography should lead to a complete description of T6SS. Abstract : The Type VI secretion system (T6SS) is a dynamic nanomachine present in many Gram-negative bacteria. Using a contraction mechanism similar to that of myophages, bacteriocins or anti-feeding prophages, it injects toxic effectors into both eukaryotic and prokaryotic cells. T6SS assembles three large ensembles: the trans-membrane complex (TMC), the baseplate and the tail. Recently, the tail structure has been elucidated by cryo electron microscopy (cryoEM) in extended and contracted forms. The structure of the trans-membrane complex has been deciphered using a combination of X-ray crystallography and EM. However, the structural characterisation of the baseplate lags behind and should be the target of future studies. Finally, cryo-tomography should provide low/medium resolution maps allowing to assemble the different parts ultimately leading to a complete structural description of T6SS.